Comparing self-report and parental report of psychopathologies in adolescents with substance use disorders - Kuitunen-Paul, Sören; Eichler, Anna; Wiedmann, Melina; Basedow, Lukas A.; Roessner, Veit; Golub, Yulia (European Child & Adolescent Psychiatry, 2021)
Both internalizing and externalizing psychopathologies interfere with the treatment of substance use disorders (SUD) in adolescents. Self-reports of psychopathologies are likely biased and may be validated with parental reports. We compared N = 70 standardized self-reports of adolescents entering outpatient SUD treatment (13.2–18.6 years old, 43% female) to parental reports on the same psychopathologies, and explored biases due to gender, age, SUD diagnoses and SUD severity. Bivariate bootstrapped Pearson correlation coefficients revealed several small to moderate correlations between both reporting sources (r = 0.29–0.49, all pcorrected ≤ 0.039). A repeated measures MANOVA revealed moderately stronger parental reports of adolescent psychopathologies compared to adolescent self-reports for most externalizing problems (dissocial and aggressive behaviors, p ≤ 0.016, η2part = 0.09–0.12) and social/attention problems (p ≤ 0.012, η2part = 0.10), but no differences for most internalizing problems (p ≥ 0.073, η2part = 0.02–0.05). Differences were not associated with other patient or parental characteristics including age, gender, number of co-occurring diagnoses or presence/absence of a certain SUD (all puncorrected ≥ 0.088). We concluded that treatment-seeking German adolescents with SUD present with a multitude of extensive psychopathologies. The relevant deviation between self- and parental reports indicate that the combination of both reports might help to counteract dissimulation and other reporting biases. The generalizability of results to inpatients, psychiatry patients in general, or adolescents without SUD, as well as the validity of self- and parental reports in comparison to clinical judgements remain unknown.
CRIS-Team Scopus Importer:2021-09-10
Keywords: Addiction; Behavioral problems; Emotional problems; Inter-rater agreement; Questionnaire; Substance use disorder